A dominant mesomelic dysplasia associated with a 1.0-Mb microduplication of HOXD gene cluster at 2q31.1. Issue 9 (24th June 2010) - Cho, Tae-Joon; Kim, Ok-Hwa; Choi, In Ho; Nishimura, Gen; Superti-Furga, Andrea; Kim, Kang Suhp; Lee, Young-Ju; Park, Woong-Yang
Abstract : A three-generation family with four patients affected by a novel mesomelic dysplasia was investigated for genome-wide DNA copy number variation profiles. This revealed a microduplication of a 1.0-Mb chromosomal segment at 2q31.1 spanning nine Homeo box D (HOXD) genes that co-segregated with the phenotype. Quantitative PCR analysis of a gene within this duplicated region showed consistent results. Mesomelic dysplasia Kantaputra type (MDK; MIM 156232), which shares some phenotypes with this family, has also been mapped to a chromosomal region comprising 2q31.1, raising the possibility that MDK and the condition observed in this family may be allelic.